Optimizing mixing duration to achieve efficient nitrite accumulation and functional microbiome enrichment in mainstream partial denitrification - Naveed Ali; Dara Memarzadeh; Anh Van Le; Jafar Ali; Stephan Fuchs; Mohammad Azari (Journal of Environmental Chemical Engineering, 2025)

Detektivarbeit im bakteriellen Proteom - Susanne Engelmann; Stephan Fuchs (BIOspektrum, 2025)
Genome sequences encode the full blueprint of life. However, functional annotation, especially of short open reading frames (sORFs), remains uncertain. Many small proteins are likely overlooked by standard algorithms. Proteomics using LC-MS/MS enables protein detection but depends on existing databases, which underrepresent sORFs. We developed a proteogenomic workflow integrating MS/MS data with genome-wide ORF predictions to detect novel small proteins. Applied to Staphylococcus aureus and other bacteria, it revealed numerous previously unannotated sORFs, expanding our understanding of microbial proteomes.

chemtrain: Learning deep potential models via automatic differentiation and statistical physics - Paul Fuchs; Stephan Thaler; Sebastien Röcken; Julija Zavadlav (Computer Physics Communications, 2025)

The role of stormwater infrastructure in regional methane emissions - Lorenzo Rovelli; Carlo Morandi; Attaallah Abusafia; Stephan Fuchs; Ulrich Dittmer; Andreas Lorke (Water Research, 2023)

Cut of OPEX—Sophisticated Technical Solutions for Hot Strip Mills - Stephan Krämer; Wolfgang Fuchs; Heiko Reichel; Christopher Klein; Angela Ante; Michael Degner (BHM Berg- und Hüttenmännische Monatshefte, 2018)

Relatedness of wildlife and livestock avian isolates of the nosocomial pathogen Acinetobacter baumannii to lineages spread in hospitals worldwide - Gottfried Wilharm; Evelyn Skiebe; Paul G. Higgins; Marie T. Poppel; Ulrike Blaschke; Sarah Leser; Christine Heider; Magdalena Heindorf; Paul Brauner; Udo Jäckel; Karin Böhland; Christiane Cuny; et al. (Environmental Microbiology, 2017)
Summary The natural habitats and potential reservoirs of the nosocomial pathogen Acinetobacter baumannii are poorly defined. Here, we put forth and tested the hypothesis of avian reservoirs of A . baumannii . We screened tracheal and rectal swab samples from livestock (chicken, geese) and wild birds (white stork nestlings) and isolated A . baumannii from 3% of sampled chicken ( n = 220), 8% of geese ( n = 40) and 25% of white stork nestlings ( n = 661). Virulence of selected avian A . baumannii isolates was comparable to that of clinical isolates in the Galleria mellonella infection model. Whole genome sequencing revealed the close relationship of an antibiotic‐susceptible chicken isolate from Germany with a multidrug‐resistant human clinical isolate from China and additional linkages between livestock isolates and human clinical isolates related to international clonal lineages. Moreover, we identified stork isolates related to human clinical isolates from the United States. Multilocus sequence typing disclosed further kinship between avian and human isolates. Avian isolates do not form a distinct clade within the phylogeny of A . baumannii , instead they diverge into different lineages. Further, we provide evidence that A . baumannii is constantly present in the habitats occupied by storks. Collectively, our study suggests A . baumannii could be a zoonotic organism that may disseminate into livestock.

Visualization of tumor heterogeneity by in situ padlock probe technology in colorectal cancer - Amin El-Heliebi; Karl Kashofer; Julia Fuchs; Stephan W. Jahn; Christian Viertler; Andrija Matak; Peter Sedlmayr; Gerald Hoefler (Histochemistry and Cell Biology, 2017)

Toponymic GIS — Role and potential of place names in the context of geographic information systems and GIS - Stephan Fuchs (KN - Journal of Cartography and Geographic Information, 2015)

Stoffeinträge in die Gewässer aus urbanen Räumen in Russland und Deutschland - Stephan Fuchs; Ramona Wander; Tatyana Rogozina (WASSERWIRTSCHAFT, 2011)

Einsatz des nofdp IDSS im Rahmen der Konzeption naturverträglicher Hochwasserschutzmaßnahmen an der Mümling - Kaj Lippert; Michael Haase; Thorsten Hens; Monika Thül; Elmar Fuchs; Peter Horchler; Christoph Hübner; Manfred Ostrowski; Stephan Rosenzweig; Matthias Sottong; Axel Winterscheid (WASSERWIRTSCHAFT, 2009)

nofdp IDSS — ein kostenfreies Softwareprodukt zur Konzeption von naturverträglichen Hochwasserschutzmaßnahmen - Axel Winterscheid; Elmar Fuchs; Michael Haase; Thorsten Hens; Peter Horchler; Christoph Hübner; Piet van Iersel; Kaj Lippert; Manfred Ostrowski; Stephan Rosenzweig; Monika Thül (WASSERWIRTSCHAFT, 2009)

Abundance, distribution, and territory areas of rock-dwelling Lake Tanganyika cichlid fish species - Christian Sturmbauer; Corinna Fuchs; Georg Harb; Elisabeth Damm; Nina Duftner; Michaela Maderbacher; Martin Koch; Stephan Koblmüller (Hydrobiologia, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

MouseNet© database: digital management of a large-scale mutagenesis project - Walter Pargent; Stephan Heffner; Karlheinz F. Schäble; Dian Soewarto; Helmut Fuchs; Martin Hrabé de Angelis (Mammalian Genome, 2000)

The clinical-chemical screen in the Munich ENU Mouse Mutagenesis Project: screening for clinically relevant phenotypes - Birgit Rathkolb; Tanja Decker; Edith Fuchs; Dian Soewarto; Christiane Fella; Stephan Heffner; Walter Pargent; Rüdiger Wanke; Rudi Balling; Martin Hrabé de Angelis; Helmut J. Kolb; Eckhard Wolf (Mammalian Genome, 2000)